Inovasi Produk Ekonomi Kreatif dengan Pemanfaatan Pepaya Muda Menjadi Permen Manis - Darman Syafe’i; Rr Dimas Veronoca P; Wiwit Manda Sari; Salsa Nadillah; Indiana Indiana; Puja Dwi Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Papaya is a fruit that is very popular with people because it contains many benefits. In Marga Bhakti Village there are quite a lot of papaya fruit trees, one of which is in the yard, but the residents of Marga Bhakti Village use papaya fruit only for consumption in the form of fresh fruit or cooked as a vegetable. The aim of this creative economic activity is to utilize papaya into high quality products. For this reason, candy is chosen which is very popular with the public. It is hoped that it can improve the economy in Marga Bhakti Village, Sinar Peninjauan District, Ogan Komering Ulu Regency.